Design of SCADA System for Oil Pipeline Control Using LabVIEW - Sabri, Laith Abed; Mohammed, Subhi Aswad; Issa, Mohammed Ibrahim (Al-Nahrain Journal for Engineering Sciences, 2017)
The paper describes a design and simulation of a Supervisory Control And Data Acquisition (SCADA) system to control oil pipeline and depot plant. The aim of the process is to control oil transportation through a shared pipeline and to minimize products contamination. The study attempts to fulfill an optimal sequence of batches of refined products to satisfy the customer demands in term of: volume , maximum flow rate, optimizing the total operational cost, and reducing products contamination.The proposed system introduces a control algorithm to perform process control system functions and for achieving the tasks and actions in specific sequences and precedence. The control algorithm performs processing of pumping station control, sharing single oil pipeline, maintaining tanks level, and depot inventory control. This paper investigate many factors which effects the length of transmix segment, which enable to offer optimum solutions to reduce products contamination.LabVIEW software is used for performing various signals acquisition and monitoring, also for simulating and designing the control system strategy.